Variegated kopsia garden plant - Hussain, A; Jose, P A; Remya, R (Indian Horticulture, 2019)
There is no remarkable difference except in leaf variegation in general vegetative and reproductive characters of normal plants and its mutants. The variegated feature forms novelty to the mutants and becomes a valuable addition to ornamental gardening, assuming more significance among plant breeders and field taxonomists for further study.